INTEGRATING MOBILE APPS IN LANGUAGE EDUCATION: BENEFITS AND CHALLENGES - Temirova Malika Rustamovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract. The rapid development of mobile technology has transformed language education by providing learners with flexible, interactive, and personalized learning opportunities. Mobile applications (apps) have become valuable tools for enhancing vocabulary, grammar, pronunciation, listening, speaking, reading, and writing skills. Their accessibility and user-friendly interfaces allow students to engage in language learning anytime and anywhere. Despite these advantages, integrating mobile apps into language education also presents several challenges, including technological limitations, learner distraction, unequal access to digital devices, and concerns about educational quality. This article examines the benefits and challenges of using mobile applications in language education and provides recommendations for educators to maximize their effectiveness.